2021
DOI: 10.1186/s12877-021-02529-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementing advance care planning in early dementia care: results and insights from a pilot interventional trial

Abstract: Background Advance care planning (ACP) is particularly appropriate for persons with early dementia (PWED) since it promotes conversations about dementia-specific illness scenarios, addresses inconsistencies between advance directives and patients’ observed behavior, emphasizes prospective and relational autonomy, and may be generally consistent with older persons’ decision-making needs. However, despite evidence of its benefits, ACP is yet to become widely used among PWED. In this paper, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…A recently published pilot trial on a nurse-led interview to promote ACP in patients with early dementia showed that the intervention was well received by patients and their significant others. Participants expressed satisfaction with the procedure, especially regarding the opportunity to discuss a sensitive topic with the help of a facilitator [ 45 ]. However, only 16 patients were enrolled out of 105 screened; the trial revealed misconceptions about dementia and ACP in patients, significant others, and healthcare professionals, as well as structural and institutional challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published pilot trial on a nurse-led interview to promote ACP in patients with early dementia showed that the intervention was well received by patients and their significant others. Participants expressed satisfaction with the procedure, especially regarding the opportunity to discuss a sensitive topic with the help of a facilitator [ 45 ]. However, only 16 patients were enrolled out of 105 screened; the trial revealed misconceptions about dementia and ACP in patients, significant others, and healthcare professionals, as well as structural and institutional challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Okonkwo et al, 2007, 2008; Tallberg et al, 2013), reasoning (Gurrera et al, 2006; Marson et al, 1995), and the appreciation and expression of choice (Marson et al, 1996). Moreover, declining decision-making capacity in individuals with cognitive impairment combined with the uncertainty of when to best initiate discussions about ACP, the need for more adapted explanations and specific intervention programs for ACP as well as insufficient training for physicians in these situations (Bosisio et al, 2021; for a review, see Tilburgs et al, 2018; Wendrich-van Dael et al, 2020) further complicate ACP for individuals with cognitive impairment.…”
Section: The Present Studymentioning
confidence: 99%
“…In our opinion, explicitly discussing WTL may contribute to a better understanding of the residents, both for staff and residents' loved ones. As an illustration, many advance care planning models include open-ended questions about the WTL (Bosisio et al 2021). Consideration should also be given to including this topic for discussion at other times, such as when a resident first enters the LTCF or during follow-up, as a catalyst for discussions about the resident's current experience.…”
Section: Implication For Clinical Practice and Researchmentioning
confidence: 99%